Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.biomaterials.2013.01.028
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and emphysematous and fibrotic injury on the re-cellularization of de-cellularized lungs

Abstract: Use of de-cellularized cadaveric lungs as 3-dimensional scaffolds for ex vivo lung tissue generation offers a new potential therapeutic approach for clinical lung transplantation. However, it is likely that some of the available cadaveric human lungs may be from older donors or from donors with previously existing structural lung diseases such as emphysema or pulmonary fibrosis. It is not known whether these lungs will be suitable for either de-cellularization or re-cellularization. To investigate this, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(137 citation statements)
references
References 19 publications
10
127
0
Order By: Relevance
“…the stroma, as one hallmark of tumourigenesis, which directly affects cancer-enabling pathomechanisms and metastasis. Moreover, the ECM within decellularised lungs of aged mice compromised proper repopulation of lung epithelial cells, similarly to emphysematous scaffolds [289]. This supports the notion that the ECM not only serves as a scaffold and essential mirror of cell-specific changes and phenotypes, but actively signals to the cell via integrins or mechanoreceptor-mediated outside-in signalling [290][291][292].…”
Section: Ecm Dysregulation As a New Hallmark Of Lung Ageingsupporting
confidence: 63%
See 1 more Smart Citation
“…the stroma, as one hallmark of tumourigenesis, which directly affects cancer-enabling pathomechanisms and metastasis. Moreover, the ECM within decellularised lungs of aged mice compromised proper repopulation of lung epithelial cells, similarly to emphysematous scaffolds [289]. This supports the notion that the ECM not only serves as a scaffold and essential mirror of cell-specific changes and phenotypes, but actively signals to the cell via integrins or mechanoreceptor-mediated outside-in signalling [290][291][292].…”
Section: Ecm Dysregulation As a New Hallmark Of Lung Ageingsupporting
confidence: 63%
“…Beyond the gain of skin wrinkles due to loss of matrix elasticity, enhanced matrix deposition and altered matrix composition have been reported for the ageing heart, kidney, skeletal muscle, and, most importantly, for the lung in humans and animal models [284][285][286][287][288][289]. With respect to lung cancer, HANAHAN and WEINBERG [163] emphasised the influence of the tumour microenvironment, i.e.…”
Section: Ecm Dysregulation As a New Hallmark Of Lung Ageingmentioning
confidence: 99%
“…14,18,20 To generate standard curves, 2% SDC and 1% SDS solutions were diluted in de-ionized (DI) water over a range consistent with use in decellularization schemes. 4,5,7,8,10,13,[20][21][22][23][24][25][26][27][28][29] The samples were then mixed with 0.0125% MB (Sigma-Aldrich) in DI water (w/v) at a ratio of either 1:1, 1:10, or 1:100 (sample:MB solution, v/v). After vortexing of the samples with MB, chloroform (Sigma-Aldrich) was added at a ratio of 1:2 (sample: chloroform, v/v).…”
Section: Anionic Detergent Assay Development and Optimizationmentioning
confidence: 99%
“…MSCs within lungs have also been identified that have the ability to express markers of ATI and ATII cells (73,95,214). In this regard, a particularly relevant finding is that MSCs may be less finicky toward the scaffold milieu in terms of attachment (19,21,170,180,213,217). However, what is not yet established is whether MSCs fully redifferentiate into specific lung cell types within a scaffold and recapitulate the functions of the native cell type.…”
Section: Recellularization In Lung Bioengineeringmentioning
confidence: 99%